THE INFLUENCE OF DYSLIPIDEMIA ON THE PERIODONTAL STATUS IN TYPE 2 DIABETES MELLITUS PATIENTS - Amelia Surdu; Ioana Martu; Irina Ursarescu; Monica Scutariu; Silvia Martu; Adriana Balan (Romanian Society of Oral Rehabilitation, 2015)
Introduction Diabetes mellitus and hyperlipidemia are independent risk factors for the periodontal disease; patients with type 2 diabetes mellitus frequently present an impaired lipid profile. Aim of the study We proposed an evaluation of the periodontal status in type 2 diabetic patients, with and without dyslipidemia. Material and methods The study was conducted on 43 patients, divided in two groups: study group (patients with type 2 diabetes mellitus and hyperlipidemia) and the control group (patients with diabetes but without hyperlipidemia). The lipid profile was assessed and every patient was submitted to periodontal clinical examination. Results The study group presented significantly higher values of the periodontal parameters (probing depth, clinical attachment loss, bleeding on probing) than the control group. Discussions Patients with dyslipidemia (already in high risk of periodontal disease due to the presence of diabetes mellitus) can present a significant risk to periodontal tissue breakdown. There is also to be mentioned that a vicious circle becomes existent, the periodontal disease itself enhancing the systemic inflammatory status and predisposing to a poor glycaemic control. Conclusions The patients with diabetes mellitus and hyperlipidemia exerted higher values of the parameters relevant for the periodontal inflammation and tissue loss than the patients without dyslipidemia.